Correlations of Handling Procedures and Sleep Patterns of the Infants Admitted to the Neonatal Intensive Care Unit - Zahra Godarzi; Khadijeh Zarei; Mamak Shariat; khosro Sadeghniat; Niko Nikafs; Hamideh Sepaseh (Mashhad University of Medical Sciences, 2018)
Background: The present study aimed to assess handling procedures and their effects on the sleep-wake time in the preterm infants admitted to the neonatal intensive care unit (NICU). Methods: This observationalcross-sectional study was conducted in the NICU ofVali-e-Asr Teaching Hospital affiliated to Tehran University of Medical Sciences (TUMS), Iran in 2016. Sample population consisted of 15 preterm infants, and duration of the handling procedures was considered to be 15 days or 360 hours. Handling procedures were recorded within an uninterrupted 24-hours period. Sleep patterns of the infants were checked at 8 AM-8 PM using Als' behavioral states scale of Newborn Individualized Developmental Care and Assessment Program (NIDCAP sheet). Results: Mean frequency of the handling procedures during 24 hours was 59.93±15.86. Within 12 hours, mean frequency of the care/monitoring, therapeutic, and supportive procedures was 41.20±12.14 during the day, while it was 18.73±5.43 at night. Mean handling procedures in minutes was 18.73±5.43 for care/monitoring procedures, 13.60±13.28for therapeutic procedures, and 76.21±93.08 for supportive procedures. In therapeutic and care/monitoring handling procedures, sleep duration decreased in the infants, while it increased in the supportive procedure. Mean total oxygen saturation was 94.80±2.81, and mean total heart rate was 147.30±16.76. Conclusion: According to the results, supportive handling could increase sleep duration in preterm infants. Therefore, it is recommended that this technique be applied for the comfort of preterm infants in the presence of parents.